PENGARUH AKREDITASI DAN KELOMPOK REFERENSI TERHADAP KEPUTUSAN SISWA MELANJUTKAN KULIAH (STUDI KASUS PADA SMA YAYASAN PENDIDIKAN KELUARGA MEDAN) - cho, chon (STIE-PMCI, 2023)
This study aims to determine the effect of accreditation and reference group on the decision to continue collage. Population in this study were students of SMA Yayasan Pendidikan Keluarga Medan which amounts to 150 students while the technique of sample sampling by randoms sampling with sampling technique using slovin method. So the sample in this study amounted to 35 people. This type of research is a quantitative research. Quantitative research is a research that aims to determine the degree of relationship and pettern/shape of infuence between two or more variables, which with this research will be built a theory that serves to explain, predict and control a symptom. The result of determination coefficient with correlation regression value equal to 0,802, meaning that together accreditation and reference group on the decision to college at SMA Yayasan Pendidikan Keluarga Medan have contribution to the strong level. Then coeficient of determination Adjusted R Square ( aqual to 0,621 (62,1%). So it can be said that 62,1% variation of bound variable that is accreditation and reference group have contribution to decision to continue collage at SMA Yayasan Pendidikan Keluarga Medan while the rest of 37,9% have contribution by other variable outside model.